PENYULUHAN GIZI IBU HAMIL DAN BALITA DALAM KEGIATAN POSYANDU DELIMA NUSA ENDAH RW 05 KELURAHAN KARYA MULYA KECAMATAN KESAMBI CIREBON - Yosi Yusrotul Khasanah; Ika Choirin Nisa; Siti Nurdiyana; Heny Puspasari; Agi Yulia Ria Dini; Renita Maula Cahyani (Rena Cipta Mandiri, 2026)
Nutrition education for pregnant women and toddlers is an important promotive and preventive effort to improve public health and prevent nutritional problems such as anemia, Chronic Energy Deficiency (CED), and stunting. This activity was conducted at Posyandu Delima Nusa Endah RW 05, Karya Mulya Village, Cirebon, targeting pregnant women, breastfeeding mothers, and mothers with toddlers. The aim of the program was to increase community knowledge and awareness regarding balanced nutrition during pregnancy and toddler growth and development.The methods used included interactive lectures, group discussions, simulations with visual media, and simple demonstrations of balanced nutritional diets. Program evaluation was carried out using pre-tests and post-tests to measure participants’ understanding before and after counseling. The results showed an increase in participants’ knowledge after the intervention. Participants demonstrated better understanding about the importance of consuming balanced nutrition, animal protein, iron supplementation tablets, and applying appropriate nutritional parenting practices to prevent stunting. The success of the counseling activities was supported by participatory educational methods, attractive learning media, and the active involvement of Posyandu cadres in assisting the community. In conclusion, nutrition education at Posyandu is an effective public health strategy to increase awareness and encourage healthy living behaviors among pregnant women and families with toddlers.